Sytuacja społeczno-gospodarcza Albanii w kontekście integracji z Unią Europejską - Dragoshi, Gert (Gospodarka w Praktyce i Teorii, 2012)
European Integration of Albania is one of the specific and the most diffi cult process among theWestern Balkan countries. To have a complete picture of this process one should have in mind an overview of trends in the relationship between the Western Balkans and the European Union. The very important role plays also the prospect of membership of these countries for their social, political and economic situation. This article aims to present the socio-economic situation of Albania and the reforms this country should undertake to be prepared for the membership in the EU.